2018
DOI: 10.1590/s0102-053620180113
|View full text |Cite
|
Sign up to set email alerts
|

Initial development of lettuce in vermicompost at higher trichoderma doses

Abstract: The study aimed to evaluate the initial development, as well as, the chemical characteristics of lettuce plants grown in substrate with high concentrations of bioagent (trichoderma). A completely randomized design with four replicates was used. The treatments, applied to a substrate composed of a blend of vermicompost and commercial substrate, were established by the following doses of the commercial product ICB Nutrissolo Trichoderma: T1) 0.0; T2) 1.0; T3) 2.0; T4) 4.0; T5) 8.0 and T6) 16.0x1011 conidia kg -1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…Similar results to the present study were found by Wiethan et al (2018), who observed that all trichoderma concentrations tested in lettuce seedlings grown in the same concentration of vermicompost had a reducing effect on the root and shoot development when compared to the treatment without trichoderma. Higher than recommended doses of 8 and 16 10 11 conidia kg -1 reduced germination, concentration of these nutrients in the leaves and inhibited the development of vegetables compared to other treatments.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Similar results to the present study were found by Wiethan et al (2018), who observed that all trichoderma concentrations tested in lettuce seedlings grown in the same concentration of vermicompost had a reducing effect on the root and shoot development when compared to the treatment without trichoderma. Higher than recommended doses of 8 and 16 10 11 conidia kg -1 reduced germination, concentration of these nutrients in the leaves and inhibited the development of vegetables compared to other treatments.…”
Section: Discussionsupporting
confidence: 92%
“…Antibiotics and fungal synthesized plant growth regulators that are reported to be responsible for increasing plant nutrient uptake (Machado et al, 2012;Singh et al, 2016;Wiethan, 2018), plant organ size and crop yield (Vinale et al, 2014) may also cause phytosanitary or physiological damage to plants as a result of phytotoxicity and pathogenicity (Frankenberger & Muhammad, 1995). For example, Hassan et al (2013) found that trichoderma overdose causes inhibition of Striga hermonthica seed germination.…”
Section: Low Organic Content Can Cause Interspecific Competition With Advantage Tomentioning
confidence: 99%